Therapeutic Idea and Approaches to Obesity with Acupuncture - 施茵 张琳珊 韩丑萍（译） (Journal of acupuncture and tuina science, 2005)
Combining the personal clinical practice, the authors of this article illustrated the basic principle of treating obesity with acupuncture, studied its therapeutic effect evaluation, and demonstrated the idea and approaches in clinical application. In addition, the authors concluded that syndrome differentiation was the treatment principle and correct approach was crucial to the final result.